PENGARUH CORPORATE GOVERNANCE DAN PROFITABILITAS TERHADAP LEVERAGE (STUDI PADA PERBANKAN YANG TERCATAT DI BURSA EFEK INDONESIA PERIODE 2015-2019) - Ningsih, Tuty Hardiyanti; Hajar, Ibnu (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis Universitas Halu Oleo)
This study aims to determine the effect of Corporate Governance and Profitability on Leverage. Corporate Governance in this study is measured by the Audit Committee, Board of Directors and Independent Board of Commissioners. The object of this study is the banking sector listed on the Indonesia Stock Exchange for the 2015-2019 period. The sample in this study were 28 companies selected by using purposive sampling method. The data used in this research is secondary data. The analysis technique was carried out using panel data regression analysis techniques which were processed using the eviews 9 application. The results of this study indicate that the Audit Committee has a positive and insignificant effect on Leverage, the Board of Directors has a significant positive effect on Leverage, the Independent Board of Commissioners has a negative and significant effect on Leverage, Profitability has a significant and negative effect on Leverage.